2001
DOI: 10.1055/s-2001-14635
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective β-Lactone Formation from Phenyldiazoacetates via Catalytic Intramolecular Carbon-Hydrogen Insertion

Abstract: Dirhodium(II) catalysts with chiral carboxylate or carboxamidate effectively promote b-lactone formation from phenyldiazoacetates in high yield and with up to 63% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Decomposition of 75 in the presence of chiral bis(oxazoline) copper(I) complexes was also shown to be a viable option, although regioselectivities in this case were poor. As previously observed, 127 changing to the phenyl-substituted diazoacetate carbenoid precursor (R = Ph) resulted in exclusive β-lactone production (Table 15, entries e and f). b Reaction conducted in refluxing pentane.…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…Decomposition of 75 in the presence of chiral bis(oxazoline) copper(I) complexes was also shown to be a viable option, although regioselectivities in this case were poor. As previously observed, 127 changing to the phenyl-substituted diazoacetate carbenoid precursor (R = Ph) resulted in exclusive β-lactone production (Table 15, entries e and f). b Reaction conducted in refluxing pentane.…”
Section: Methodssupporting
confidence: 62%
“…83,121,122,127 In 2001, Doyle and coworker published a report of enantioselective β-lactone formation from phenyl diazoacetates. 127 Despite the introduction of considerable ring strain via its formation and the deactivating effect of the adjacent electron-withdrawing ester group, successful β-lactone formation was observed from isopropyl and cyclohexyl diazoacetate precursors 71 and 72, respectively [Scheme 7(a) and 7(b)] In both instances, β-lactone formation was the dominant process over competing γ-lactone formation and moderate enantioselectivities were possible in the presence of Rh 2 (S-DOSP) 4 . The phenyl functionality at the α-diazo position of the isopropyl and cyclohexyl substrates is of critical importance in producing the targeted fourmembered ring.…”
Section: Figure 18mentioning
confidence: 99%
“…In 2001, Doyle and May reported that aryldiazoacetates are quite selective substrates for formation of b-lactones 55 ( Fig. 4) over their five-membered ring counterparts [70]. They examined a number of chiral dirhodium catalysts, and Rh 2 (S-DOSP) 4 (26) in refluxing pentane generally provided the best enantioinduction, with enantioselectivities ranging from 41 to 69% ee.…”
Section: Other Recent Enantioselective Examplesmentioning
confidence: 98%
“…The intramolecular cyclization with cyclohexyl aryldiazoacetate system 57 (Table 4.6 ) preferably formed the β -lactone system 58 when the azetidinone -based dirhodium(II) carboxamidate catalysts were used [119] . The same was also observed with carboxylate catalysts [120] .…”
Section: Synthesis Of Lactone and Lactam Heterocyclesmentioning
confidence: 99%
“…Chemoselectivities were high ( > 97% product selectivity), and the products were formed in 66 -69% yield. However, good control of enantioinduction was not achieved, only 42 -51% ee with the carboxamidate catalysts tested, and 63% ee with Rh 2 ( S -DOSP) 4 [119,168] . The acyclic system 60 only formed γ -lactone product 61 (Table 4.7 ).…”
Section: Synthesis Of Lactone and Lactam Heterocyclesmentioning
confidence: 99%